2019
DOI: 10.4103/ijpc.ijpc_22_19
|View full text |Cite
|
Sign up to set email alerts
|

“Adjunctive effects of a short session of music on pain, low-mood and anxiety modulation among cancer patients” – A randomized crossover clinical trial

Abstract: Aims:Pain, a distressing symptom frequently suffered by cancer patients, is inherently associated with anxiety and depression yet often not alleviated with pharmacotherapy alone. This study was aimed at assessing the effect of an instrumental classical music listening session as an adjunct to the ongoing therapies, on pain, anxiety, and mood modulation in cancer patients.Materials and Methods:A randomized crossover open clinical trial was designed involving adult resident patients suffering pain at a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…The duration of these effects is difficult to ascertain due to the varying lengths of follow up across measures and studies. However, one study found that reduced levels of anxiety and pain were sustained for at least 12 h after music listening (Fernando et al, 2019 ). Several of these studies reported positive emotional effects of music listening compared to a control (no music listening group).…”
Section: Resultsmentioning
confidence: 99%
“…The duration of these effects is difficult to ascertain due to the varying lengths of follow up across measures and studies. However, one study found that reduced levels of anxiety and pain were sustained for at least 12 h after music listening (Fernando et al, 2019 ). Several of these studies reported positive emotional effects of music listening compared to a control (no music listening group).…”
Section: Resultsmentioning
confidence: 99%
“…This finding shows that music is effective in reducing pain in patients receiving chemotherapy during the COVID‐19 process. Studies on music practices in cancer patients in the literature show that music has a positive effect on the pain levels of cancer patients (Binns‐Turner et al, 2008; Bradt et al, 2015; Fernando et al, 2019; Vachiramon et al, 2013). It has been stated that music creates various neuronal effects in patients with chronic cancer pain and is effective on patients' pain levels (Hunt et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Using music in cancer treatment process provides relaxation in patients and reduces symptoms such as stress, pain and anxiety caused by cancer and its treatments (Arslan & Özdemir, 2015). In the carried out studies, it has been shown that music practices have a positive effect on reducing pain (Binns‐Turner et al, 2008; Bradt et al, 2016; Danhauer et al, 2010; Gutgsell et al, 2013; Krishnaswamy & Nair, 2016; Li et al, 2012; Moradian et al, 2015) and anxiety levels (Binns‐Turner et al, 2008; Bradt et al, 2016; Danhauer et al, 2010; Krishnaswamy & Nair, 2016; Palmer et al, 2015; Zhou et al, 2015) in cancer patients (Fernando et al, 2019; Jasemi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Schmerz und Stress sind vielfach von Angst begleitet, sodass diese Trias beim kritisch kranken Patienten in der Intensivmedizin eine wesentliche Rolle spielt [ 6 , 11 , 43 ]. In einer kürzlich vorgestellten Untersuchung an 59 Patienten, die sich einer HNO-Operation unterziehen mussten, wurden 29 Patienten additiv mit einer Musikbeschallung (2-mal 30 min täglich) behandelt [ 14 ].…”
Section: Beeinflussung Von Schmerzen Durch Musikunclassified